Optimization Depolymerization of Tilapia Fish Scale Chitosan by Oxidative Degradation with H2O2 using Central Composite Design (CCD) - Dhian Eka Wijaya; Afra Raeviana Putri; Intan Lestari; Edwin Permana; Munifilia Ekasari; Nur Ahniyanti Rasyid (ALCHEMY Jurnal Penelitian Kimia, 2026)
Tilapia fish scales are among the fishery wastes that have not been optimally utilized, even though they have economic potential when processed into chitosan. Chitosan is a poly(2-amino-2-deoxy-β-D-glucose) obtained by deacetylation of chitin, with a high molecular weight ranging from 100 to 1.200 kDa, making it difficult to dissolve in water. To increase its solubility, chitosan can be depolymerized into oligochitosan with a lower molecular weight, around 5 – 10 kDa. This depolymerization process is influenced by temperature, time, and concentration factors. This study aims to determine the optimal conditions for the depolymerization of chitosan from tilapia fish scales using a central composite design (CCD). The stages of chitosan production include demineralization, deproteinization, and deacetylation, yielding a white powder with a molecular weight of 264.214 kDa and a degree of deacetylation of 74.24%. Based on CCD optimization, the optimal conditions for the depolymerization of tilapia fish scale chitosan were 3.6 M H2O2, 50 °C, and 2 hours, yielding a molecular weight of 3093 kDa. Fourier transform infrared (FTIR) characterization showed a peak shift from wave number 3267 cm-1 to 3303 cm-1. Oligochitosan also showed 100% solubility in water at neutral pH